제주도 밭의 외래잡초 분포 - 김창석(Chang-Seok Kim); 정영재(Young-Jae Chung); 이인용(In-Yong Lee); 이정란(Jeong-ran Lee); 송희근(Hee-Kun Song); 오영주(Young-Ju Oh) (Weed & turfgrass science, 2015)
We surveyed the distribution of exotic weeds in the 141 crop fields of Jeju island. The exotic weeds were summarized as 66 taxa including 18 families, 50 genera, 64 species and 2 varieties. In winter crop fields there were 45 species of exotic seeds in 18 families, in summer crop fields 50 species in 16 families, and in perennial crop fields 39 species in 17 families. Total exotic weeds were classified to 39.4% of summer annuals, 36.4% of winter annuals, 7.6% of summer and winter annuals, and 16.7% of perennials. The ratio of summer annuals were high in the summer crop fields. Compositae was dominant family, followed by Gramineae, Malvaceae and Solanaceae. Malvaceae did not appear in perennial crop fields. Dominant exotic weeds in winter crop fields were Chenopodium album, Amaranthus viridis, Senecio vulgaris and Coronopus didymus, in summer crop fields, Chenopodium album, Amaranthus viridis, Senecio vulgaris and Sonchus oleraceus and in perennial crop fields, Conyza sumatrensis, Gnaphalium calviceps and Senecio vulgaris. The dominant exotic weeds in the crop fields of Jeju island were Chenopodium album, followed by Amaranthus viridis, Senecio vulgaris, and Conyza sumatrensis. This information could be useful for establishment of exotic weed control methods in Jeju island. 제주도의 밭을 대상으로 141지점을 선정하여 조사를 진행하였다. 제주도 밭에 발생하는 외래잡초 조사결과 18과 50속 64종 2변종, 총 66분류군의 외래잡초가 조사되었고 동계작물 재배지에서는 18과 45종, 하계작물 재배지에서는 16과 50종, 다년생 작물 재배지에서는 17과 39종이 출현하였다. 외래잡초의 생활형은 하계일년생 잡초가 39.4%, 동계일년생은 잡초는 36.4%, 하계일년생과 동계일년생이 모두 가능한 잡초는 7.6%, 다년생 잡초는 16.7%로 분석되었다. 특히 하계작물 재배지에서 하계일년생 잡초의 비율이 높았다. 종의 과별 분포순위는 국화과, 벼과, 아욱과가 우점하는 것으로 분석되었으나 다년생 작물 재배지에서는 아욱과는 출현하지 않았다. 제주도의 동계작물 재배지에서 우점하는 외래잡초는 흰명아주, 청비름, 개쑥갓, 냄새냉이, 들개미자리였고 하계작물 재배지에서는 흰명아주, 청비름, 개쑥갓, 방가지똥이었다. 다년생 작물 재배지에서는 큰망초, 선풀솜나물, 개쑥갓, 흰명아주로 조사되어 다른 작물과 차이를 보였다. 제주도 전체 밭에서 발생하는 외래잡초의 우점종은 흰명아주, 청비름, 개쑥갓, 큰망초, 방가지똥 등으로 분석되었다. 제주도에 발생하는 외래잡초의 발생정보는 밭의 지속적인 관리방안을 수립하는데 도움이 될 것이다.